The Development of Herbal Compress Ball, Stone Spa for Thai Traditional Medicine Providers, Luang Pho Pern Hospital, Nakhon Pathom Province - Boonmag, Sujitra; Srikaew, Papicthaya; Sae-ngo , Sililak; Bunpean, Aumpol; Choedchutirakul, Warintorn (Arts of Management Journal, 2020)
The objective of this research is to 1) Develop the spa rock herbal compress, 2) Compare the levels of satisfaction of service providers and clients towards the spa rock herbal compress and former compress where the samples were 20 traditional medical service providers and 60 clients. This study conducted on the research and development The data was collected 1) Through group conversation 2) Satisfaction questionnaires where the statistics employed were frequency, percentage, mean, standard deviation, and Pair Sample T-Test. The results illustrated that: 1) the former compress lacked the agility while pressing and the handle was unsteady after being steamed for a long period and applied for 2 times and above; 2) the spa rock herbal compress consists of 2 components, i.e., the base section which is similar to bowl having 9 buttons made from stainless, a diameter of 10 cm, and 2 cm of depth, used for containment of spa rocks. The handle is made from wood with the length of 14 cm, a diameter of 3 cm and the bag to contain 50 g of the herbs is made from sphere calico having a diameter of 30 cm.; 3) the results of comparison of satisfactions of service providers towards the spa rock herbal compress and former compress indicated the statistically significant difference (P-value < 0.05) and the results of comparison of satisfaction of clients towards the spa rock herbal compress and former compress indicated no statistically significant difference (P-value < 0.05). The results could be applied as the alternative for the production of the spa rock herbal compress which is simple, low-cost, and high-quality.